1997
DOI: 10.1007/bf00426065
|View full text |Cite
|
Sign up to set email alerts
|

Pathoanatomic findings in radiohumeral epicondylopathy

Abstract: Several authors believe that a compression syndrome of the radial nerve or its muscle branches is responsible for the clinical picture of radiohumeral epicondylopathy. Various structural and functional stenoses have been discussed as possible causes. We performed systematic electromyographies (EMGs) on the extensors subdividing from the radial epicondyle and found significant changes (P < 0.05) in 27/51 patients regarding latency, velocity of nerve conduction and rate of polyphasic potentials. Especially affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…All lateral elbow pain has been traditionally interpreted as tendopathic in nature. However, in numerous papers published since 1996 the conclusions regarding etiology and pathology have become more controversial 35 . More recent literature has suggested that lateral elbow pain can emerge as the consequence of musculotendinous, neural or chondropathic etiologies, each posing a different pathological and clinical picture.…”
Section: Upper Quarter Work‐related Msdsmentioning
confidence: 99%
“…All lateral elbow pain has been traditionally interpreted as tendopathic in nature. However, in numerous papers published since 1996 the conclusions regarding etiology and pathology have become more controversial 35 . More recent literature has suggested that lateral elbow pain can emerge as the consequence of musculotendinous, neural or chondropathic etiologies, each posing a different pathological and clinical picture.…”
Section: Upper Quarter Work‐related Msdsmentioning
confidence: 99%